Hubungan Pola Makan Dengan Kejadian Gastritis Pada Remaja di Pondok AL-Hikmah, Trayon,Karanggede, Boyolali - Diatsa, Bagas; , Abi Muhlisin, SKM, M.Kep; , Vinami Yulian, S.Kep,Ns., M.Sc (2016)
Gastritis is inflammation of the gastric. Gastritis disease occurs in people who have irregular eating patterns and food that stimulates the production of stomach acid. In Indonesia, gastritis was one of the ilness which was suffered by Indonesian people, especially in Central Java, 2009. The rate of gastritis sufferer reached up to 31,2%. Based on the introductory study from Al Hikmah Boarding School, Trayon, Karanggede, Boyolali, 2015, there were 30 people who infected gastritis. The research was aimed to know the relation between eating pattern gastritis incident in teenagers in Al Hikmah Boarding. This research used non experimental method with cross sectional design. The analysis result which was done with the spearman test showed that there was a significant relation, this relation was shown by the correlation score that was 0,636 which was included to the strong category. Having done the research, the researcher found the result that was the bad eating pattern could cause the high gastritis incident. Key words: gastritis, eating pattern